2019
DOI: 10.1002/jobm.201900189
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the saccharopine dehydrogenase gene improves lysine biosynthesis inFlammulina velutipes

Abstract: Saccharopine dehydrogenase (EC 1.5.1.7) regulates the last step of fungal lysine biosynthesis. The gene (Fvsdh) encoding saccharopine dehydrogenase was identified and cloned from the whole genome of Flammulina velutipes. The genomic DNA of Fvsdh is 1257 bp, comprising three introns and four exons. The full-length complementary DNA of Fvsdh comprises 1107 bp with a deduced amino acid sequence of 368 residues. A 1,000-bp promoter sequence containing the TATA box, CAAT box, and several putative cis-acting element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The N-terminal polyamine biosynthesis domain is exactly the spermidine synthase tetramerization domain (IPR035246). The C-terminal saccharopine dehydrogenase domain includes the saccharopine dehydrogenase NADP binding domain (IPR005097) and the saccharopine dehydrogenase C-terminal domain (IPR032095), and it acts as saccharopine reductase in the penultimate step of the lysine biosynthesis pathway named by Liu et al [ 26 ] in F. filiformis . It means that gene2942 is a natural chimeric protein of spermidine synthase (SPDS) and saccharopine reductase (SR), named FfSPDS-SR. Additionally, its fourth exon, as the longest one (1433 bp) in which no termination codon appeared, acts as a bridge between Spds and Sr to form a natural fusion gene.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal polyamine biosynthesis domain is exactly the spermidine synthase tetramerization domain (IPR035246). The C-terminal saccharopine dehydrogenase domain includes the saccharopine dehydrogenase NADP binding domain (IPR005097) and the saccharopine dehydrogenase C-terminal domain (IPR032095), and it acts as saccharopine reductase in the penultimate step of the lysine biosynthesis pathway named by Liu et al [ 26 ] in F. filiformis . It means that gene2942 is a natural chimeric protein of spermidine synthase (SPDS) and saccharopine reductase (SR), named FfSPDS-SR. Additionally, its fourth exon, as the longest one (1433 bp) in which no termination codon appeared, acts as a bridge between Spds and Sr to form a natural fusion gene.…”
Section: Resultsmentioning
confidence: 99%
“…Lysine production was 63% higher in mutant ECRS-gltA and 38% higher in mutant BSRS-gltA, indicating a higher metabolic flux into the lysine biosynthesis pathway. Liu et al overexpressed the gene Fvsdh encoding saccharopine dehydrogenase in F. filiformis , which increased the gene expression level by 1.1–3-fold and the lysine content in the transformants by 1.12–1.3-fold [ 33 ]. This work found that lysine content increased by nearly 13% under optimal citric acid induction conditions, with the gene expression levels of hcs , hac, and hah being 2.67, 1.97, and 1.90 times higher than the control, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine is a limiting amino acid and one of the essential amino acids necessary for the normal growth and development of the human. However, human and animal bodies cannot synthesize lysine ( Liu et al, 2019 ). Therefore, mung bean is of great significance for the synthesis of lysine after Se application.…”
Section: Discussionmentioning
confidence: 99%